Netnography, an etnographic model in the digital era [La netnografía, un modelo etnográfico en la era digital] (2017)
This article aims to describe the netnographic research process from an ethnographic research view. Thus, the ethnographic process literature from some authors proposals was analyzed in the light of understanding this qualitative research methodology. Moreover, it was described the netnographic process presented by recognized authors and lastly a model was proposed integrating relevant aspects from both positions: the ethnographic and netnographic. The two processes have similarities in general structure, however netnographic process tends to have a difficult to define the field of research and determine the amount of conversations to be analyzed. © 2017.